2013
DOI: 10.1097/eja.0b013e3283592733
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy of noninvasive haemoglobin measurement by pulse oximetry depends on the type of infusion fluid

Abstract: The bias of measuring haemoglobin concentration by pulse oximetry is dependent on whether a crystalloid or a colloid fluid is infused. Trial registration ClinicalTrials identifier: NCT01195025.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A volunteer study showed that hydroxyethyl starch causes SpHb to overestimate Hb, while acetated Ringer's solution produced the opposite result. 14 In fasting healthy volunteers, both fluids cause vasodilation. The difference in SpHb bias could then be attributable to extravasation of crystalloid fluid that could strengthen the background (non-pulsatile) signal of the Radical-7 measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A volunteer study showed that hydroxyethyl starch causes SpHb to overestimate Hb, while acetated Ringer's solution produced the opposite result. 14 In fasting healthy volunteers, both fluids cause vasodilation. The difference in SpHb bias could then be attributable to extravasation of crystalloid fluid that could strengthen the background (non-pulsatile) signal of the Radical-7 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…11 -13 Its accuracy is affected by the simultaneous infusion of fluid; slightly higher SpHb values are obtained when the PI is high. 14 The PVI is typically twice as high in the conscious patient as it is in the anaesthetized state, 10 which suggests that the nervous system might be involved in the generation of the parameter output.…”
mentioning
confidence: 99%
“…A comparison between Hb measured invasively and by pulse oximetry has been published elsewhere [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Massimo calculates the PI value by rating the pulstatile and non-pulstatile pulses. In various studies evaluating PI as an indicator of peripheral perfusion, it has been reported that basal measurements of the PI may show high variability [14,35].…”
Section: Discussionmentioning
confidence: 99%